PERAN BIDANG KBKK DALAM MENDUKUNG PELAKSANAAN PROGRAM KELUARGA BERENCANA DI DINAS P3AKB KABUPATEN SIDOARJO - Rodiyah, Siti Nur; Murti, Indah (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2026)
The Family Planning (KB) Program is one of the government's strategic policies to control population growth while improving family quality. This article aims to analyze the role of the Family Planning and Family Resilience (KBKK) Division in supporting the implementation of the KB program at the Women's Empowerment, Child Protection, and Family Planning Office (DP3AKB) of Sidoarjo Regency. The methods used in this article are observation, activity implementation, and documentation during the activities. The results of this community service activity indicate that the KBKK Division plays a significant role in supporting the program's implementation. Activities such as the Development Planning Deliberation (Musrenbang) and Main Ideas (Pokir) are important means of conveying program information to the public. However, there are still obstacles in data management and coordination between units that are not optimal. Therefore, it is necessary to improve the administration system, data integrity, and strengthen human resource capacity to support the success of the KB program more effectively and sustainably.